2021
DOI: 10.1021/acs.jpclett.1c02240
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Force Spectroscopy Reveals Distinctions in Key Biophysical Parameters of αβ T-Cell Receptors Compared with Chimeric Antigen Receptors Directed at the Same Ligand

Abstract: Chimeric antigen receptor (CAR) T-cell therapies exploit facile antibodymediated targeting to elicit useful immune responses in patients. This work directly compares binding profiles of CAR and αβ T-cell receptors (TCR) with single cell and single molecule optical trap measurements against a shared ligand. DNA-tethered measurements of peptide-major histocompatibility complex (pMHC) ligand interaction in both CAR and TCR exhibit catch bonds with specific peptide agonist peaking at 25 and 14 pN, respectively. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
(88 reference statements)
1
14
0
Order By: Relevance
“…1b). Since the TCRβ subunit has also been proposed to undergo FG-loop-regulated conformational change 6,24,25 , we assume that disruption of the α 1 α 2 – β 2m joint would also result in tilting of the TCR–pMHC bonding interface and shifting of the mechanical load from the TCR Vβ–Cβ joint to the Vα–Cα joint, leading to partial unfolding of the Vα–Cα joint (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1b). Since the TCRβ subunit has also been proposed to undergo FG-loop-regulated conformational change 6,24,25 , we assume that disruption of the α 1 α 2 – β 2m joint would also result in tilting of the TCR–pMHC bonding interface and shifting of the mechanical load from the TCR Vβ–Cβ joint to the Vα–Cα joint, leading to partial unfolding of the Vα–Cα joint (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Besides binding properties of the TCR–pMHC complex, its structural features and conformational changes have been suggested to be important for TCR triggering. For example, TCR–pMHC docking orientation has been correlated to its ability to trigger T cell signaling 15,22,23 .Partial unfolding or allosteric regulation of either the TCR and/or MHC molecules has been inferred from mechanical experiments and steered molecular dynamics (SMD) simulations of pulling single TCR–pMHC bonds 6,8,24,25 . Whereas the extent of these conformational changes has been correlated to the strength of TCR–pMHC catch bonds 6,8,24 , the two phenomena have not been integrated into a mathematical model to explore their potential connection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 13 We used CHO cells expressing single-chain peptide MHC (pMHC) as antigen-presenting cells (APCs) ( Figures S1 B and S1C). 14 We found that anti-pMHC CARs have similar biophysical properties to TCR 15 but that the CD8 co-receptor is dispensable for CAR signaling. 14 CD8 is typically considered to be important for bringing LCK into the IS.…”
Section: Resultsmentioning
confidence: 88%
“…Whether scDb are able to activate CTLs better than natural recognition by αβTCRs remains to be seen. Contrary to conventional receptor–ligand interactions exemplified by antigen–antibody binding, bioforces are essential for nonthermal equilibrium, mechanosensor-based αβT cell activation ( 81 90 ). αβT cell motility during immune surveillance and the local cytoskeletal machinery place physical load on individual αβTCR-pMHC bonds, tuning the sensitivity and specificity of αβTCR recognition ( 82 ).…”
Section: Discussionmentioning
confidence: 99%